Iga Myeloma with Increased Anion Gap, Pseudo hyperphosphatemia and Pseudohyponatremia - Rachna, Kapoor; Gaurav, Dhawan; Padmaja, Kodali (Journal of Human Health Research, 2018)
A myeloma case is described with laboratory artifacts including increased anion gap, pseudohyperphosphatemia, and pseudohyponatremia. The report explains mechanisms behind paraprotein‑related assay interference and diagnostic pitfalls.
Keywords: IgA Myeloma; Anion Gap; Pseudohyperphosphatemia; Pseudohyponatremia; Paraprotein Interference